The style, method, and programme of Xiphilinus' epitome of Cassius Dio's Roman History - Mallan, C (Duke University, 2013)
Xiphilinus’ selections and omissions reveal a distinct authorial program, especially on issues of biography, kingship, and erudition that accord with vital concerns of other authors of the eleventh century.